Good agricultural practices and its compatibility with Halal standards. (August 2020) - Alzeer, Jawad; Rieder, Ulrike; Hadeed, Khaled Abou
Abstract: Background: Food from agriculture is fundamental to our survival and play a very important role in our daily life. It acts as a source of energy and provides us with essential nutrients. The consumers' attitudes towards food and agriculture are changing based on regional, cultural and religious influences. Food production following Halal principles is emerging as one of the most important challenges and holds a leading position in the global business today. Scope and approach: Halal's main objective is to ensure that the process and ingredients are entirely clean, pure and comply with Islamic principles. A transparent system of Halal auditing has been developed to ensures a manufactured product that complies with all Halal requirements. To harmonize and facilitate the process of Halal certification, a compatible system between Halal standard and agricultural good practice or other recognized safety standards, need to be established. Key findings and conclusion: The future demand for Halal products is high and has a strong presence in developed and developing countries. To harmonize Halal system with others, all issues related to Halal production of food and agriculture are presented. Highly critical topics such as manure, pesticides, lubricant, and genetically modified product have been highlighted and their Halal status with regards to their nature, process, and composition have been discussed. Furthermore, Halal compatibility with good agricultural practices has been determined. Highlights: The relation between good agricultural practices and good Halal practices was investigated. Issues related to Halal production were addressed. To simplify understanding, ingredients were classified into highly critical, critical and non-critical. Highly critical issues, ingredients and processes were addressed and their Halal status were presented. GAP or any accredited form will be a prerequisite for the Halal certification.